Does Fatigue Complaint Reflect Memory Impairment in Multiple Sclerosis?. (1st March 2014) - Jougleux-Vie, Caroline; Duhin, Emeline; Deken, Valerie; Outteryck, Olivier; Vermersch, Patrick; Zéphir, Hélène
Abstract : Background and Purpose . Fatigue and memory impairment are common symptoms in multiple sclerosis (MS) and both may interact with cognition. This can contribute to making a complaint misrepresentative of the objective disorder. We sought to determine whether fatigue complaint in MS reflects memory impairment and investigated whether patients' subjective fatigue is associated with memory complaint. Methods . Fifty MS patients complaining of fatigue underwent subjective assessment of fatigue and memory complaint measured using self-assessment scales. Cognitive functions were assessed using a battery of neuropsychological tests, including a test of verbal episodic memory, the selective reminding test (SRT). Correlations were studied between subjective fatigue, memory complaint, and performance in verbal episodic memory. Results . Depression score, psychotropic and/or antiepileptic drug use, Expanded Disability Status Scale (EDSS) score, and MS form were confounding factors. After adjusting for these confounding factors, neither fatigue complaint nor memory complaint was correlated with SRT performance. Subjective fatigue was significantly associated with memory complaint. Conclusion . Although complaint of fatigue in MS was correlated with memory complaint, subjective fatigue was not the expression of memory impairment.